ELEMENTS OF PSYCHOANALYSIS IN ARTISTIC THINKING OF THE REPRESENTATIVES OF INTELLECTUAL PROSE OF TWENTIES OF XX CENTURY - Ushnevych, S.E. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Psychoanalytical discourse in the Romance philology of separate representatives of intellectual prose of twenties of XX century is researched in the article; ways of realization of author’s understanding of theory of Froid of unconscious were cleared up; modernist –erotic model and oneiric dominant in the world of text reality were analyzed.